(untitled) (Jurnal Bina Praja, 2023)
Abstract: This research aims to analyze an influence of female leadership on public service performance moderated by good governance using the context of local government studies in Indonesia (districts and cities). The findings of this research increase our understanding of the influence of female leadership, public sector governance, and performance in local government service delivery. By using 4,910 local government observation data in Indonesia from 2009 to 2019, the empirical findings of this research showed that female leadership has a positive and significant influence on the achievement of public service performance. Furthermore, these results indicate that having female leadership can help the organization achieve better strategies and goals. In addition, good governance can strengthen the influence of female leadership on the performance of public services. This research implies that the existence of female leadership supported by good governance skills can provide maximum service to the public.